Site-Specific Glycosylation Patterns of the SARS-CoV-2 Spike Protein Derived From Recombinant Protein and Viral WA1 and D614G Strains - Tian, Yuan; Parsons, Lisa M.; Jankowska, Ewa; Cipollo, John F. (Frontiers in Chemistry, 2021)
The SARS-CoV-2 spike protein is heavily glycosylated, having 22 predicted N-glycosylation sites per monomer. It is also O-glycosylated, although the number of O-glycosites is less defined. Recent studies show that the spike protein glycans play critical roles in viral entry and infection. The spike monomer has two subdomains, S1 and S2, and the receptor binding domain (RBD) within the S1 domain. In this study we have characterized the site-specific glycosylation patterns of the HEK293 recombinant spike RBD and S1 domains as well as the intact spike derived from whole virus produced in Vero cells. Vero cell derived spike from WA1 strain and a D614G variant was analyzed. All spike proteins, S1 and RBDs were analyzed using hydrophilic interaction chromatography (HILIC) and LC-MS/MS on an Orbitrap Eclipse Tribrid mass spectrometer. N-glycans identified in HEK293 derived S1 were structurally diverse. Those found in the HEK293 derived RBD were highly similar to those in HEK293 S1 where N-glycosites were shared. Comparison of the whole cell derived WA1 and D614G spike proteins revealed that N-glycosites local to the mutation site appeared to be more readily detected hinting that those sites are more exposed to glycosylation machinery. Moreover, recombinant HEK293 derived S1 was almost completely complex glycan whilst both WA1 and D614G derived from VeroE6 cell whole virus were predominantly high mannose glycans. This stands in stark contrast to glycosylation patterns seen in both CHO and HEK cell derived recombinant S1, S2 and whole spike previously reported. Concerning O-glycosylation, our analyses revealed that HEK293 recombinant proteins possessed a range of O-glycosites with compositions consistent with Core type-1 and -2 glycans. The O-glycosites shared between the S1 and RBD constructs, sites T323 and T523, were occupied by a similar range of core-1 and -2 type O-glycans. Overall, this work reveals that the sample nature and cell substrate used for production of these proteins can have a dramatic impact on glycosylation profile. SARS CoV2 spike glycans are associated with host ACE 2 receptor interaction efficiency. Therefore, understanding such differences will serve to better understand these host-pathogen interactions and inform choice of cell substrates to suite downstream investigations.